Abordaje fisioterapéutico en lumbalgia de adolescentes deportistas de la Federación Deportiva de Los Ríos, en el periodo de junio-septiembre del 2024. - Chimbo Tixi, Gustavo Israel (2024)
Low back pain in adolescent athletes has become a growing problem worldwide, particularly in the context of intensive and early specialized sports. Our research addresses the problem of back pain in young athletes of the Sports Federation of Los Ríos, Ecuador, during the period June to September 2024. Internationally, back pain is one of the main causes of disability and affects an important percentage of young athletes. In the Ecuadorian national context, the data reflect a high prevalence of this problem among youth athletes, aggravated by the lack of adequate training and physiotherapy resources. It focuses on implementing a physiotherapeutic approach in the treatment and prevention of back pain in this specific population group, with the aim of improving the health and sports performance of affected young people. A mixed methodology including both quantitative and qualitative approaches is proposed to evaluate the effectiveness of physiotherapy interventions and their impact on quality of life and sports performance.